Wide Excision with Immediate Reconstruction of the Mandible Using Free Fibular Flap in Ameloblastoma of the Mandible—A Need of Time: Our Experience of 37 Cases - Hemant A. Saraiya (Indian Journal of Plastic Surgery)
Background Ameloblastoma is a benign yet locally aggressive odontogenic tumor of the jaw with high recurrence rates. Despite many studies, the search is still on for the treatment approach which can render the acceptable recurrence rates with good functional and esthetic results. Methods In this prospective study, we operated on 37 patients of mandibular ameloblastoma between 2009 and 2018. Two patients were treated with curettage and chemical sterilization of the cavity. Resection of a tumor with a 2-cm margin was performed in the rest of 35 patients. The mandibular defect was primarily reconstructed with the microvascular free fibular flap in 29 patients. Results The follow-up ranged from 6 months to 7.7 years with a mean of 5.1 years. A tumor recurred within a year in all two patients (100%) treated with curettage. Out of 35 radical excisions, only one patient (2.85%) developed recurrence 3 years after the disease-free interval. Good mouth opening, intelligible speech, satisfactory lower jaw shape, and facial profiles were achieved in all 29 patients who were treated with primary free fibular flap. Conclusion We prefer wide excision with 2-cm margins on each side of a tumor with the primary reconstruction of the mandible in all cases of mandibular ameloblastoma. The free fibular microvascular flap is our treatment of choice as all defects of the mandible can be reconstructed with the free fibular flap. Wide excision is the key to prevent a recurrence.